Preparo e caracterização dos diferentes polimorfos do cloridrato de metformina utilizando técnica de recristalização por evaporação de solventes - Nardino, Deise (2018)
In this work the thermal behavior and the characterization of the pharmaceutical raw material metformin hydrochloride (IFT) and its crystals prepared from different solvents were performed. The IFT characterization was prepared using the techniques of X-ray Diffraction, Simultaneous Differential Exploration Calorimetry, Infrared Spectroscopy, Evolved Gas Analysis and Optical Microscopy. The results obtained by the characterization of the IFT were used as references for further comparison with the crystals prepared from the IFT by the solvent evaporation recrystallization technique. From this technique, two dissolution and storage temperature tests were prepared for crystal growth. The crystal characterization was performed by the techniques X-Ray Diffraction, Simultaneous Differential Exploratory Calorimetry and Optical Microscopy. The studies have investigated that the IFT is in polymorphic form I, and with the exposure of the IFT to the combination of different solvents and certain dissolution and storage temperature conditions, results in different crystalline forms of said drug, in addition the studies present another polymorphic form characterized as Form II. This inference was concluded from crystal diffractograms, thermal analysis graphs and optical microscopy images. It was observed different diffractograms when compared to the reference, different melting points, besides the obtaining of different crystals, allowing to safely identify and characterize the obtained polymorph. With these results it was possible to verify that there was polymorphism. In this way, the polymorphic Form I and Form II of the drug metformin hydrochloride was characterized, proving the postulated hypothesis and the good performance of the techniques of experimentation and analysis used.